2016
DOI: 10.1007/s40429-016-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Factors Associated with Cannabis Involvement

Abstract: Approximately 50-70% of the variation in cannabis use and use disorders can be attributed to heritable factors. For cannabis use, the remaining variance can be parsed in to familial and person-specific environmental factors while for use disorders, only the latter contribute. While numerous candidate gene studies have identified the role of common variation influencing liability to cannabis involvement, replication has been elusive. To date, no genomewide association study has been sufficiently powered to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Alterations in coupling may predate exposure to cannabis use and reflect genetic or environmental factors that increase risk for substance use. It has been estimated that 50%–70% of the variation in CB use can be attributed to genetic factors and about 20% of variation reflect shared environmental factors (Bogdan, Winstone, & Agrawal, ). Pagliaccio et al () found that predispositional factors accounted for the relationship between amygdala volume and CB use.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in coupling may predate exposure to cannabis use and reflect genetic or environmental factors that increase risk for substance use. It has been estimated that 50%–70% of the variation in CB use can be attributed to genetic factors and about 20% of variation reflect shared environmental factors (Bogdan, Winstone, & Agrawal, ). Pagliaccio et al () found that predispositional factors accounted for the relationship between amygdala volume and CB use.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of causality, cannabis use is clearly a necessary condition for CUD, but as not all cannabis users develop CUD, use is not clearly sufficient. The etiology of CUD is complex ( Agrawal and Lynskey, 2006 ; Bogdan et al , 2016 ; Haberstick et al , 2011 ; Verweij et al , 2013b ), involving both genetic ( Sherva et al , 2016 ) and environmental factors. Social-ecological models of substance use ( Babor, 2010 ; Connell et al , 2010 ; Corbett, 2001 ; Gruenewald, 2011 ; Gruenewald et al , 2014 ) assume that in general, use is increased by factors that increase availability and also desirability, by normalizing use and reducing perception of harm.…”
Section: Adverse Health and Psychosocial Problems Associated With Canmentioning
confidence: 99%
“…One burgeoning area for further research is that of genetic and epigenetic components of CUD. The fact that only a subpopulation of chronic cannabis users develop CUD or express CWS strongly suggests genetic predispositions might be at play (Agrawal & Lynskey, 2006;Blecha et al, 2019;Bogdan et al, 2016) / There are relatively few human genetics studies aiming to identify heritable genetic factors linked to CUD, including familial transmission analysis (Gfroerer, 1987), twin studies (Vink et al, 2010), whole genome sequencing (Gizer et al, 2018;Sherva et al, 2016), and genome-wide association studies (Bogdan et al, 2016;Sherva et al, 2016). Clearly, there will be polygenic contributions to CUD and CWS, as is the case for all substance abuse disorders.…”
Section: Con Clus I On S and Sug G E S Ti On S For Future Re S E Archmentioning
confidence: 99%